ORGANIZATION NEPHROLOGIC ASSISTANCE IN KYIVCITY: PROBLEMS AND THEIR SOLUTIONS - I.O. Dudar; B.I. Palamar; E.K. Krasjuk; O.M. Loboda (Ukrainian Journal of Nephrology and Dialysis, 2016)
The article are covering problems for the organization of nephrological care in Kyiv. Regulations according to which nephrological assistance is provided to city residents are listed. Proposals to improve the nephrological aid in Kншv are presented